The Missouri River Journals of John James Audubon - Audubon, John James, 1785-1851 (Book collections on Project MUSE., 2016)
"The first accurate transcription of John James Audubon's 1843 journals, which includes recently discovered and previously unpublished journal entries detailing his last expedition along the upper Missouri River"--Provided by publisher.